Efectos del Código Civil y Comercial en temas societarios vinculados con la ley concursal - Prono, Javier R. (Universidad Nacional del Litoral, 2020)
The work addresses the effects of the Civil and Commercial Code in corporate matters related to bankruptcy law. We have worked with a transversal perspective with the intention of making it a useful didactic tool for students